Clinical Diagnostic Value of Stromelysin-2 and Highly Sensitive-Cardiac Troponin I in the Severity of Coronary Artery Obstruction - Hammoodi, Amal A.; Saleh, Basil O.; Al-Alwany, Ameen A. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Coronary artery disease is a leading cause of death worldwide. Troponin is released into blood from patients with reversible myocardial ischemia. Stromelysin-2 is also involved in the development and progression of atherosclerosis by tissue remodeling and degradation of extracellular matrix proteins.Objectives: To investigate the role of serum high-sensitive cardiac troponin I (hs-cTn I) and Stromelysin-2 (Str-2) in the diagnosis and determination of the severity of coronary artery obstruction.Methods: This cross-sectional study was conducted on 125 subjects undergoing coronary angiography for suspicion of coronary artery disease in Baghdad Teaching Hospital/ Medical City complex/ Baghdad/ Iraq by the Department of Biochemistry/ College of Medicine/ University of Baghdad between March and December 2024. The participants were divided into three groups: Group I included 48 subjects with no coronary artery lesion or with < 50% stenosis), Group II included 47 subjects with > 50% stenosis in a single or double coronary arteries, and Group III included 30 subjects with > 50% stenosis in ≥ three coronary arteries or ≥ 50% stenosis in the left main stem. Serum levels of hs-cTn I and Str-2 were measured by the ELISA technique.Results: The median and 1st – 3rd quartile values of hs-cTn I and Str-2 levels of group III and group II were significantly higher than those of groups I (p= 0.001). The median value of hs-cTn I was significantly higher in group III than in group II (p